Fiberless Recombinant Adenoviruses: Virus Maturation and Infectivity in the Absence of Fiber - Valérie Legrand; Danièle Spehner; Y. Schlesinger; Nathalie Settelen; Andréa Pavirani; Majid Mehtali (1999)
ABSTRACT In vivo targeting of therapeutic genes to specific tissues has become a major issue in gene therapy, in particular when recombinant adenovirus vectors are used. Restriction of the viral tropism to selected cell types requires the abrogation of the interaction between the viral fiber and its natural cellular receptors and the introduction of a new binding specificity into the virion. In this context, fiberless adenoviruses are attractive vectors, since they may be used as substrates for the insertion of a new ligand in other capsid proteins. In this study, we confirm by using cloned full-length adenovirus genomes with the fiber gene deleted that efficient virus particle formation can occur in the absence of fiber. As expected, the infectivity of such fiberless viruses was severely reduced, but it could be only partially restored when the viruses were produced in cells stably providing the fiber in trans . Although incorporation of penton base into the fiberless particles was normal and binding of the particles to the cellular integrins was functional, several pieces of experimental evidence suggest that later steps in the cell entry process are impaired in correlation with an incorrect maturation of several structural proteins of the fiberless particles. These observations support the hypothesis that the fiber protein may have additional biological functions besides its role in cell binding. Together with the fiber complementation cells, such fiberless vectors constitute unique tools to investigate the role of the fiber in virus assembly, maturation, and cell entry and to explore the possibility of deriving gene transfer vectors with novel target specificities.